CONTE SUA HISTÓRIA: modos de viver e narrar experiências com doenças crônicas - de Souza, Elizeu Clementino (Autobiografie. Ricerche, pratiche, esperienze, 2020)
The text discusses issues related to experiences with the disease, the biographical learning processes, and the ways of coping built by the subjects to live with chronicity. The objective is to analyze narratives published in the ‘Saber Viver’ Journal, in the ‘Tell your story’section, which regards HIV/AIDS, mobilizing theoretical dispositions of the (auto)biographical approach are mobilized for the analysis of the narratives, as a source of research, as far as it concerns the experiences of the subjects with the illness. Furthermore, the reflection aims to discuss questions about the processes of production, circulation and reception of the journal, by evincing the ruptures and reconfigurations which are part of a chronic disease experience, the provisions built by each subject to live with HIV/AIDS and the representations about the disease.